Oncogene v-src transforms and establishes embryonic rodent fibroblasts but not diploid human fibroblasts. - Hjelle, B (1988)
The conversion of cells from a normal phenotype to full malignancy apparently requires multiple genetic events. Efforts to reconstruct multistep tumorigenesis in cell culture have shown that two types of oncogenes (typified by HRAS and MYC) can cooperate to elicit complete transformation. Transformation of embryonic rodent cells by single oncogenes is reputed either not to occur or to require specialized circumstances. It has not been known how the large group of oncogenes that encode protein-tyrosine kinases might fit into this scheme. We now report that v-src, a prototype for the kinase oncogenes, can convert rat embryo fibroblasts to a fully transformed and tumorigenic phenotype when the gene is expressed vigorously. By contrast, v-src had no demonstrable effect on diploid human fibroblasts. Our results sustain the view that it is possible for at least some oncogenes to achieve a potency sufficient for unilateral tumorigenesis.